2017
DOI: 10.1101/125492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal BMI at the start of pregnancy and offspring epigenome-wide DNA methylation: Findings from the Pregnancy and Childhood Epigenetics (PACE) consortium

Abstract: Pre-pregnancy maternal obesity is associated with adverse offspring outcomes at birth and later in life. Individual studies have shown that epigenetic modifications such as DNA methylation could contribute. Within the Pregnancy and Childhood Epigenetics (PACE) Consortium, we meta-analysed the association between pre-pregnancy maternal BMI and methylation at over 450,000 sites in newborn blood DNA, across 19 cohorts (9,340 mother-newborn pairs). We attempted to infer causality by comparing the effects of matern… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 95 publications
1
13
0
Order By: Relevance
“…One candidate of the mechanisms is DNA methylation, which may memorize and transfer information on grandmaternal metabolism (BMI) or smoking to the next generation. Maternal BMI and smoking during pregnancy have been identified to be associated with differential DNA methylations in the offspring. It is possible that the influences of grandmaternal BMI and smoking on epigenetic changes can persist into later life of the mothers and then be transferred to the third generation.…”
Section: Discussionmentioning
confidence: 99%
“…One candidate of the mechanisms is DNA methylation, which may memorize and transfer information on grandmaternal metabolism (BMI) or smoking to the next generation. Maternal BMI and smoking during pregnancy have been identified to be associated with differential DNA methylations in the offspring. It is possible that the influences of grandmaternal BMI and smoking on epigenetic changes can persist into later life of the mothers and then be transferred to the third generation.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal hyperglycemia has been shown to decrease methylation of the leptin gene ( LEP ) in the offspring, contributing to high leptin levels in cord blood of babies born to obese mothers . Similarly, maternal BMI has been linked to methylation levels of several loci in the cord blood, the majority of which persist into adolescence independent of paternal BMI and gestational weight gain . Studies focusing on immune cells have demonstrated that high maternal BMI is inversely correlated with methylation levels within the promoter of inflammatory genes in cord blood mononuclear cells that persisted for up to 3 years of age .…”
Section: Introductionmentioning
confidence: 99%
“…A review paper describes the characteristics of the epigenome as a key component of foetal exposure in evaluating in utero exposures and childhood cancer risk . More recently, I4C members have begun cataloguing— omics signatures of early‐life factors that could be associated with CC . These signatures will be analysed across the different I4C cohorts with available biological samples.…”
Section: Resultsmentioning
confidence: 99%